PERAN PEMERINTAH KABUPATEN GRESIK DALAM KEMITRAAN BERBASIS CORPORATE SOCIAL RESPONSIBILITY - Nuraida Muji Kurnia Eka Pratiwi,; Sutomo ' '; Dina Suryawati ' (Universitas Riau, 2014)
The Role of Government in Gresik Based Partnership Corporate SocialResponsibility (CSR). This study aims to describe the implementation of CSR-based partnershipprogram by PT. Semen Gresik and Government’s role in optimizing the partnership. Thisresearch approach is qualitative approach with descriptive type, while the data analysis is touse interactive model. The results showed that the CSR program partnership model adopted byPT. Semen Gresik venture philanthropy partnerships using the plasma core, but the partnershipis still pseudo partnership and the role of government in optimizing partnerships Gresik still bemandating and partnering, in the form of a mandate to form a company with a team sub-districtand district level coordination to KISS (coordination, integration, synchronization, and synergy).However, the role of facilitating and endorsing yet implemented, so that such a partnership cannot be optimized.Keywords: corporate social responsibility, the partnership, the role of government, coordination.